VILLAGE GOVERNMENT STRATEGY IN MODERNIZING PUBLIC SERVICES IN KAMIRI VILLAGE, BALUSU DISTRICT, BARRU REGENCY - A.Aminah; Pratiwi, Dian (Meraja journal, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal